The Role of Optimism and Agility towards Readiness to Change in Implementing Merdeka Belajar Kampus Merdeka - Marhisar Simatupang (Analitika: Jurnal Magister Psikologi UMA, 2022)
Freedom to study in an independent campus is a program of the Minister of Education and Culture in 2020. Learning activities at the Merdeka Campus are a manifestation of essential student-centered learning. This study aims to determine the role of optimism and agility on readiness to change in implementing independent learning at an independent campus. Respondents of this study were the lecturers at Buana Perjuangan Karawang University s many as 190 lecturers. The scale used in this study consists of a scale of readiness to change, optimism and agility. Hypothesis testing using multiple linear regression, found that optimism and agility had a positive role in readiness to change (p < 0.05). This shows that the higher the attitude of optimism and agility will increase the readiness to change in lecturers at Buana Perjuangan Karawang University. These findings can be taken into consideration in making measures to increase readiness to change by applying an attitude of optimism and agility to work on lecturers